1989
DOI: 10.1080/10408398909527490
|View full text |Cite
|
Sign up to set email alerts
|

Modified atmosphere packaging of fruits and vegetables

Abstract: Modified atmospheres (MA), i.e., elevated concentrations of carbon dioxide and reduced levels of oxygen and ethylene, can be useful supplements to provide optimum temperature and relative humidity in maintaining the quality of fresh fruits and vegetables after harvest. MA benefits include reduced respiration, ethylene production, and sensitivity to ethylene; retarded softening and compositional changes; alleviation of certain physiological disorders; and reduced decay. Subjecting fresh produce to too low an ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
604
3
71

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 938 publications
(692 citation statements)
references
References 78 publications
14
604
3
71
Order By: Relevance
“…This is consistent with literature reports which state that ethylene synthesising enzyme in fruits is inactivated at temperatures around 40°C (Gorny 1997;Kader et al 1989). …”
Section: Weight Losssupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with literature reports which state that ethylene synthesising enzyme in fruits is inactivated at temperatures around 40°C (Gorny 1997;Kader et al 1989). …”
Section: Weight Losssupporting
confidence: 93%
“…Mango fruits were dipped in three water baths maintained at 20, 30 & 40°C (± 1°C) for 40 min with the temperature controlled throughout. The immersion time of 40 min was chosen to enable disintegration of ethylene synthesis enzymes (Kader et al 1989).The mangoes were then cooled (10°C), washed and wiped clean, before uniformly sized fruits weighing to the nearest 500 g were selected and packed in bags (thickness 40 μm) made of two films: OPP (Oriented Polypropylene)-unperforated (1,100 cm 3 / m -2 /d -1 O 2 , 2,700 cm 3 /m -2 /d -1 transmission rates and 10 gm -2 d -1 moisture permeability rates) and perforated (5,000 cm 3 /m -2 /d -1 O 2 , 6,700 cm 3 /m -2 /d -1 CO 2 transmission rates and 10 gm -2 d -1 moisture permeability rates). Ten drops of water were added to each bag in order to maintain uniform relative humidity, and the headspace was actively modified to contain three initial CO 2 partial pressures with the overall pressure being atmospheric (25% by volume, 50% and 75%, the remaining being N 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of MAP on reducing the water loss was obvious, which is considered one of the main advantages of the use of MAP in storage (Kader et al 1989). Besides, honey dip with or without MAP showed similar impact on weight loss of stemless grape berries.…”
Section: Weight Lossmentioning
confidence: 89%
“…Prolonged exposure to heat, light and oxygen resulted in 20-53% loss of the initial carotenoids (De Guevara et al 2002;MinguezMosquera and Hornero-Mendez 1993). Kader et al (1989), Wright and Kader (1997a) reported that low levels of O 2 and high CO 2 influence both the reduction of carotenoid loss by oxidation, and the inhibition of its biosynthetic pathway.…”
Section: Physical Parametersmentioning
confidence: 99%